Penyusunan Modul Pembelajaran Mata Kuliah Microteaching di STAI Ali Bin Abi Thalib Surabaya - Santoso, Budi; Roviudin, Mohamad (ALAMTARA, 2024)
This research employs the Research and Development (R&D) method based on Borg and Gall, which has been simplified into five (5) stages: needs analysis for the module, initial product design, module design development, expert validation, and revision.The research yielded the following validation results: 1) The content assessment scored 37.5%, indicating that the material still needs further revision. 2) The accuracy assessment of the module scored 94.4%, signifying that the module's accuracy is valid and feasible. 3) The expert assessment of the module's presentation scored 82.85%, indicating it is valid/feasible.From these three assessments, the final score was 71.56%, categorized as valid with partial revisions. Therefore, the final result of this research is a module with moderate validation, requiring some revisions before proceeding to the next phase of research, which is group testing, to produce a module ready for use.